Combined Effect of Neural Tissue Mobilization and Deep Friction Massage in Piriformis Syndrome: A Research Protocol - Vrushali K. Athawale; Divya Jethwani; Moh’d Irshad Qureshi; Ragini Dadgal (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background:- Piriformis syndrome is the musculoskeletal condition which is characterized by pain alongwith tingling and numbness which results because of compression of piriformis muscle. Various treatmentapproaches are present for treating the piriformis syndrome but neural tissue mobilisation is manual therapysimilar to joint mobilisation. Deep friction massage is used to breakdown adhesion and release of scartissues. This study protocol has been created to find out the combined effect of neural tissue mobilizationand deep friction massage in piriformis syndrome.Methods:– On the basis of inclusion and exclusion criteria 30 participants between 20-60 years of agehaving piriformis syndrome will be select for study and are classified into two groups. Group A (n-15) forNeural Tissue Mobilisation, Group B (n-15) for Neural Tissue Mobilisation and Deep Friction Massage.Outcome measure are Oswestry Disability Index, Numerical Pain Rating Scale and Range of motion of hipjoint. Follow up of the participants are done after every 2 days and treatment duration is of 10 days.Discussion:- Effect of intervention will be analyzed by Numerical Pain Rating Scale, Oswestry DisabilityIndex and Range of Motion of Hip joint. The result of this study will significantly provide the affirmation ofNeural Tissue Mobilisation with Deep Friction Massage in Piriformis Syndrome.